EVALUASI PENERIMAAN PETUGAS TERHADAP PENGGUNAAN E-PUSKESMAS DI UPT PUSKESMAS GONDANGLEGI TAHUN 2023: EVALUATION OF STAFF ACCEPTANCE OF THE USE OF E-PUSKESMAS AT UPT PUSKESMAS GONDANGLEGI IN 2023 - Syahbaniar, Desi; Wulandari, Irma; Riskiani, Maulidia Anggy (WELL BEING, 2024)
Background: This research aims to evaluate staff acceptance of the use of E-Puskesmas at the UPT Puskesmas Gondanglegi. Subjects and Methods: This research uses the Technology Acceptance Model (TAM) method. Based on perceived usefulness and Perceived Ease of Use. The type of research used is descriptive. The data collection technique uses a questionnaire. The subject population of this research was 10 officers who used the E-Puskesmas information system. The sample used is the entire population used as a sample. Analysis of the questionnaire results was carried out using descriptive statistical methods. Results: The percentage results of the questionnaire based on perceived usefulness were 93.4% in the excellent category and Perceived Ease of Use was 62.83% in the sufficient category. Conclusion: There are several obstacles caused by users who are still confused about operating E-Puskesmas, inadequate facilities and infrastructure related to an insufficient number of computers, the workload of officers has increased because recording of patient medical records is done manually and electronically and socialization of the use of E-Puskesmas has already been carried out, but in its operation still not optimal. Keywords: Community Health Center, Evaluation System, Technology Acceptance Model (TAM)